Novel On-chip Optical Modulator Designs - Elsayed, Mohamed Mahmoud Ibrahim Ibrahim (AUC Knowledge Fountain, 2020)
The huge increments in data traffic and communication over the past few decades have pushed the conventional electronic communication systems to their physical limits in terms of data rate, bandwidth and capacity. The continuous shrinking of feature sizes, the increase in the microelectronic integrated circuits complexity, and the increasing demand for higher speeds and data rates have all stimulated seeking new technology to replace the currently present microelectronics industry rather than improving it. Photonics is one of the most likely candidates to answer this pursuit for its compatibility with the fiber optic industry, which has shown a great success in large-scale communication since around 50 years ago. Silicon photonics, in particular, is very interesting for the scientific community for its compatibility with the foundries which are the bases for microelectronic industries around the globe. Advancements in silicon photonic would rather enable the integration of both electronic and optical system components on the same chip, which is a very important step in the transition towards all-optical on-chip systems. The huge interest in silicon photonics over the past two decades has brought forth a number of applications in various fields, such as biosensing, displays, on- and off-chip interconnection, artificial intelligence, internet of things, big data centres, and telecommunications. In practice, there are many ways of realizing and fabricating on-chip silicon waveguides. Ion exchange process is one of the most commonly used techniques in fabricating glass waveguides as it offers ease of application, low cost, and low equipment requirements. Unfortunately, numerical constraints render the modelling of this process challenging due to the presence of computational instabilities at certain conditions. In the first part of this thesis, this issue is worked out by introducing a novel numerical model based on finite element method formulation. In the second part of the thesis, we concentrate on one of the promising applications of silicon photonics, which is the telecommunications. Optical communication systems include many components such as, light sources, photodetectors, multiplexers, filters, resonators, optical interconnects, switches, couplers, splitters, and modulators. The optical modulator is considered the most essential component in an optical communication system as it converts the incoming electric digital data into an optical data stream. Its acts as a binding link between both the optical and electronic domains on the chip. Therefore, electro-optical modulators have gained enormous attention during the past few years. Weak electro-optical effects in intrinsic silicon have stimulated the search for novel materials to be responsible for the modulation of the light beam. Surface plasmon polaritons, which propagate at a metal-dielectric interface, allow the confinement of light in subwavelength dimensions. However, they introduce large losses to the system. Transparent conducting oxides, especially indium tin oxide (ITO), provide metal-like response when exposed to a gating voltage while maintaining lower losses than noble metals. In the second part of the thesis, we propose two novel electro-optical on-chip integrated modulators based on the utilization of ITO as the active material.